Drought and flooding prediction in inland valleys and determinants of farmers mitigation measures across the Sudano-Guinean and Guinean zones - Akodekou, A.D.; Dossou-Yovo, E.R. (2025)
Inland valleys are among the most productive agricultural landscapes in West Africa, yet they are increasingly exposed to hydrological extremes, notably droughts and floods, which constitute the dominant climate-related stresses affecting rice-based systems. Importantly, these hazards do not occur independently: drought and flooding can occur within the same year and, in some cases, within the same growing season, creating compounded risks that severely constrain rice productivity, investment decisions, and livelihood resilience. Despite their growing importance, there remains limited understanding of the predictors and spatiotemporal dynamics of these concurrent hazards in inland valleys, hindering the development of effective early warning systems and targeted adaptation strategies.